Establishment of a Bovine Viral Diarrhea Virus Type 2 Intranasal Challenge Model for Assessing Vaccine Efficacy - Strong, Rebecca; Graham, Simon P.; La Rocca, S. A.; Raue, Rudiger; Vangeel, Ilse; Steinbach, Falko (Frontiers in Veterinary Science, 2018)
The objective of this study was to develop a bovine viral diarrhoea virus type 2 (BVDV-2) challenge model suitable for evaluation of efficacy of BVDV vaccines; a model that mimics natural infection and induces clear leucopoenia and viraemia. Clinical, haematological and virological parameters were evaluated after infection of two age groups of calves (3 months and 9 months) with two BVDV-2 strains (1362727 and 502643). Calves became pyrexic between 8-9 days post inoculation and exhibited symptoms such as nasal discharge, mild depression, cough and inappetance. Leukopenia with associated lymphopenia and neutropenia was evident in all groups with lowest leukocyte and lymphocyte counts reached 8dpi and granulocyte counts between 11 and 16 dpi, dependent on the strain and age of the calves. A more severe thrombocytopeania was seen in those animals inoculated with strain 1362727. Leukocyte and nasal swab samples were positive by virus isolation, as early as 3 dpi and 2 dpi respectively, independent of the inocula used. All calves seroconverted with high levels of BVDV-2 neutralising antibodies. BVDV RNA was evident as late as 90 dpi and provides the first evidence of the presence of replicating virus long after recovery from BVDV-2 experimental infection. In summary, moderate disease can be induced after experimental infection of calves with a low titre (104.8 or 105.0 TCID50) of virulent BVDV-2, with leucopoenia, thrombocytopoenia, viraemia and virus shedding. These strains represent an attractive model to assess the protective efficacy of existing and new vaccines against BVDV-2.